Harnessing the Power of Honey: A Natural Antioxidant for Enhancing Aseel Sperm Motility During Preservation - Miah, Abdul Gaffar; Pramanik, Md. Ahsan Habib; Mehta, Basant Kumar; Salma, Ummay (International Journal of Applied Sciences and Biotechnology, 2025)
Semen cryopreservation is essential for poultry breeding, preserving genetic diversity, and the advancement of artificial insemination techniques. However, oxidative stress remains a major limitation during semen storage, as it negatively affects sperm motility, structural integrity, and fertilizing ability. This study investigated the potential of honey, a natural antioxidant-rich substance, in improving sperm motility of Aseel roosters during short-term storage. Semen was collected from sixteen healthy and mature Aseel roosters and diluted using modified Ringer’s solution supplemented with varying concentrations of honey (1%, 2%, 3%, 4%, and 5%). A control group without honey supplementation was maintained for comparison. Semen quality parameters, including sperm concentration, total motility, progressive motility, non-progressive motility, and percentage of immotile sperm, were evaluated at 0, 2, and 4 hours post-storage using a Computer-Assisted Semen Analyzer (CASA). The results indicated that honey significantly (P